Local anesthetic agents along with hyaluronidase for inguinal hernia block provides excellent analgesia: a double blind study - Chaudhari, Asmita V.; Chaudhari, Vipul P. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Inguinal hernia block is cost effective, but fear of intra-operative pain may hinder its widespread use. It is unknown whether hyaluronidase along with local anesthetic agent provides good analgesia for hernia block. The aim was to evaluate the effectiveness of hyaluronidase along with local anesthetic agents for inguinal hernia block in patients undergoing inguinal hernioplasty. Methods: 50 patients ASA grade I and II, age above 18 years, undergoing inguinal hernioplasty were randomized into two groups. Group A received inguinal hernia block with local anesthetic agents without hyaluronidase and Group B received inguinal hernia block with hyaluronidase and local anesthetic agents. Both groups received premedication 10 minutes before induction in the form of inj. Fentanyl, Midazolam, Ranitidine and Ondansetron Results: In Group B, out of 25 patients only 4 patients required intraoperative analgesia while in group A 16 patients required intraoperative analgesia. Post operative pain was assessed for 24 hours using the pain rating scale. The mean duration of analgesia was significantly longer in group B (16.16±6.8780 hrs) compared to group A (7.32±2.5285 hrs); pain score was compared between the two groups. Group B had lower pain scores than group A which was statistically significant (P<0.05). Conclusion: It concludes that hyaluronidase with local anesthetic agent for inguinal hernia block provides excellent intraoperative analgesia and also prolongs the post operative analgesia.